Pemberdayaan Masyarakat melalui Home Industry Sirup Parijotho Argo Mulyo dalam Meningkatkan Kesejahteraan Masyarakat di Desa Colo Kecamatan Dawe Kabupaten Kudus - Afiyah, Nur Lailatul (Kolaborasi Masyarakat, 2026)
This study analyzes the community empowerment process and its impact on welfare through the Argo Mulyo Parijotho Syrup Home Industry in Colo Village, Kudus. Employing a qualitative approach, data were collected through in-depth interviews, observation, and documentation involving the business owner, employees, farmers, and traders. The results indicate that the empowerment process occurs in three stages: awareness, capacity building, and independence. Utilizing Parijotho fruit provides economic value-added, enhances skills, and strengthens social participation. The impact of this empowerment is reflected in increased income, job creation, and market certainty for farmers. Nevertheless, the program still faces constraints regarding business scale, marketing, and the level of community independence. Therefore, sustained support—through management training, access to capital, product innovation, and the strengthening of marketing networks—is essential to ensure the long-term sustainability of this local potential-based empowerment program.